A novel risk stratification model based on tumor size and multifocality to predict recurrence in pediatric PTC: comparison with adult PTC - Du, Rui; Zhang, Ying; Kou, Jiedong; Li, Jingting; Sui, Chengqiu; Zhang, Daqi; Fu, Yantao; Zhou, Le; Fu, Qingfeng; Li, Fang; Dionigi, Gianlorenzo; Liang, Nan; et al. (Frontiers in Endocrinology, 2024)
Background Pediatric papillary thyroid cancer presents with a more advanced stage of disease than adult PTC; and it is more likely to be aggresive and distant metastases, although the survival rate is high. Methods A retrospective observational study was performed in children and adults with PTC. Fisher’s exact, chi-square, and rank-sum tests were used to examine the differences. Univariate and multivariate Cox regression analyses were applied to determine the possible risk factors for prognosis. A Kaplan-Meier curve analysis was performed to investigate the relationship between the clinicopathological characteristics and recurrence rate. Results The study involved 156 children and 1,244 adults with PTC. Compared to the group without recurrence, proportions of tumors measuring > 1 cm (48.3% vs. 90.9%) and multifocality (30.3% vs. 63.6%) were higher, N1b stage occurred more frequently (33.8% vs. 100%). However, among adult PTC patients, those with recurrence were older (76.1% vs. 59.4%) than those without recurrence. Risk factors for pediatric PTC recurrence included tumor size and multifocality. However, in adult PTC, the risk factor was LLNM. The newly constructed Stratification.N showed better performance, as illustrated by the fact that patients who were classified into Stratification.N 3 showed an obviously poorer prognosis (P=0.01 and P=0.00062), especially in those aged >14 years (P=0.0052). Conclusion Compared with adult PTC, pediatric PTC showed unique characteristics in terms of clinical pathology and recurrence. Tumor size and multifocality were strong risk factors for pediatric PTC. Accordingly, the novel proposed risk stratification method could effectively predict the recurrence of pediatric PTC.